Learning Flame Test Using a Low Cost Experiment - Meena, O. P.; Sharma, R. K. (SCHOOL SCIENCE, 2017)
Flame test is the most common way of qualitative analysis of some basic radicals. Metal salts on reacting with concentrated acids impart characteristic colours to the luminous flame and colour of the luminous flame gives valuable information in their detection. Traditionally this test was carried out using costly platinum wire but recently some new experiments of flame test have been designed in which platinum is not required. In the present study a low cost experiment of flame test was introduced for learning of pre-service teachers and results are presented below.